Passage [videorecording (DVD)] - Walker, John, 1952 July 5-; Roberts, Rick, 1965-; Alexander, Geraldine; McGoogan, Kenneth, 1947-; Berzins, Andrew Rai, 1957- (Distributed by BFS Entertainment & Multimedia, 2009)
In 1845, celebrated British explorer Sir John Franklin, along with his crew of 128 men, set sail from England in search of a fabled passage west. None of them were ever seen again. A search party found no evidence of any crew or wreckage. The mystery was eventually solved by John Rae, and they were so horrific that a public campaign was begun to discredit Rae.